PERBEDAAN PENGARUH PAPARAN MUSIK MOZART, BEETHOVEN, DAN CHOPIN SELAMA KEBUNTINGAN TERHADAP KEPADATAN DENDRIT DI CEREBELLUM Rattus norvegicus BARU LAHIR - Ancha Ayu Amishinta (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2019)
Indonesia is categorized as middle human development index. One of the causes is the fluent ignorance of brain growth and development during 1000 days of life period. This period is the best opportunity to give proper stimulations to increase the maximal brain growth and development. Exposure to classical music such as Mozart, Beethoven, and Chopin music can increase the wave of brain activity. During pregnancy, Mozart music is proven to increase the dendritic density. Analyzing the difference of dendritic density of cerebrum and cerebellum of newborn baby of Rattus norvegicus that are exposed to the Mozart, Beethoven, and Chopin music, and that is not exposed to music during pregnancy. Laboratory experimental research, posttest-only control group design. Subjects were female pregnant Rattus norvegicus, grouped into 4 random groups: 1 control group and 3 treatments groups; with 6 samples each. Subjects were super ovulated, and 65 dB intensity of music was played for an hour at 20.00-21.00 on the subjects on 10th day of pregnancy. On 20th day of pregnancy, the mothers were dissected using caesarean section. 2 heaviest newborn babies of Rattus norvegicus were taken, and their brain tissues were taken as samples. The dendritic density of cerebrum and cerebellum were observed using GolgiCox method of silver impregnation procedure.Statistical test concluded there were significant differences of dendritic density of cerebrum and cerebellum of newborn babies of Rattus norvegicus among the exposure to Mozart, Beethoven, and Chopin music, and without the exposure to music with value of p=0,004 (<0,05) in cerebrum and p=0,003 (<0,05) in cerebellum. The dendritic density of cerebrum and cerebellum of newborn babies of Rattus norvegicus that were exposed to Mozart music during pregnancy were higher than that are exposed to Beethoven and Chopin music and that were not exposed to music. It is recommended for the next research to do further research to prove the dendritic density caused by the musical stimulation during pregnancy when Rattus norvegicus grows up.